USM-UMMETRO TO ESTABLISH RELATIONS IN VARIOUS DISCIPLINES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 17 May 2016 – Universiti Sains Malaysia (USM) today received a courtesy visit from Muhammadiyah University of Metro (UMMETRO), Lampung, Indonesia’s delegation led by its Rector, Professor Dr. Karwono Pawiroq, to enhance cooperation in areas of education, research and student exchange.